FACTORS AFFECTING ON BABY'S SUCKING FOR SECRETION OF BREAST MILK AT THE HEALTH CENTER BATUA MAKASSAR - Najmawaty .; Azizah Nurdin (Jurnal Kesehatan, 2014)
This study aims to to obtain a description of the factors that influence the baby's suck-ing of the breast milk in working area of Puskesmas Batua Makassar Health Center.This study is the "Cross Sectional Study". It includes a variable dependent namely the position and attachment of the infant, breast-feeding frequency, and duration of breastfeed-ing whereas the independent variables, is the secretion breast milk. The population is all postpartum women who had been treated at the health center Batua Makassar. The number of samples is 78 people. Data were obtained through questionnaires. Data analysis using regression test liners.The results of this study indicate that there is a correlation between the position and attachment of the baby (ρ = 0.000) with the production and secretion of breast milk, while breast-feeding frequency factor (ρ = 0.833) and duration of breastfeeding factors (ρ = 0.551) have no significant relationship. It was found that the most dominant factor affecting the se-cretion of breastmilk is the position and attachment of the baby.There is a relationship between Infant Positioning and attachment during breastfeed-ing to the production as well as the scretion of the breast milk. The frequency and duration of breastfeeding did not have a significant effect on the secretion of breastmilk.Key words : secretion of breast milk, positioning and fixation of the baby on the breast, fre-quency and duration of breastfeeding.